Ricci-pseudosymmetric almost α-cosymplectic (k,μ , u)-spaces admitting Ricci solitons - Uygun, Pakize; Atçeken, Mehmet; Mert, Tugba (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 514.7 We study some types of Ricci pseudosymmetric α-cosymplectic (k,μ , u)-spaces whose metric admits Ricci solitons. We present some results obtained for Ricci solitons on Ricci pseudosymmetric, projective Ricci pseudosymmetric, concircular Ricci pseudosymmetric, and W_1-Ricci pseudosymmetric spaces. Some results on almost α-cosymplectic (k,μ , u)-spaces are also presented. Finally, we give an example for the 5-dimensional case.